Anatomic variation of the flexor digiti minimi brevis muscle: a morphological and functional study: case report - Moraes, V. V. S.; Siqueira, S. L.; Rodrigues, F. P.; Queiroz, E. B. B.; Pinto, I. C. T.; Torres, G. M. (Journal of Morphological Sciences, 2015)
Abstract Introduction: A great amount of accessory and supernumerary muscles, or even their absence, has already been described in medical literature, related to Anatomy, Surgery and Radiology. In the majority of cases, muscles with any morphological changes, in their origins, insertions, number of muscle bellies and anomalous vascular or nervous patterns, are asymptomatic. However, approximately 3% of compression neuropathy cases are results of an anomalous muscle. Material and methods: During a routine dissection, an anatomical variation was found on the left hypothenar region of an afrodescendant adult's corpse, which led the authors to further investigate its incidence and the clinical significance of this variation, basing up of articles published in refereed journals and renowned books on this subject. Results: Many authors have already identified numerous muscle variations in the hypothenar region, whether in dissection labs or in private clinics. Since some muscular variations may cause numerous clinical symptoms, it's important to have a detailed anatomical knowledge of the correspondent region. There are cases of ulnar nerve compression caused by an anomalous flexor digiti minimi brevis described in the medical literature. The majority of authors explained the nervous and vascular compression from some factors as injury, small repetitive traumas, genetically predetermined muscle size and muscular hypertrophy. Conclusion: The importance of differential diagnosis to any affections of the hypothenar region lies on the anatomical and surgical knowledge of the structures quoted in this study, the statistics related to the prevalence of these anatomical variations and the relevance of these in the present case.